Incidence Rates of Pediculosis Capitis and Helminthiasis in Children in Danukusuman Surakarta - Setya, Adhi Kumoro; Haryatmi, Dwi; Listiyaningsih, Alfina; Putri, Elisa (Jurnal Biologi Tropis, 2024)
Pediculosis capitis and helminthiasis It is categorized as a neglected disease but is still an important health problem, especially for children. These two diseases each cause clinical disorders on the surface and internal organs of the body. Danukusuman is one of the most densely populated areas in the city of Surakarta, where in previous years many cases of gastrointestinal disorders affected local residents. The aim of this study to determine the incidence of pediculosis capitis and helminthiasis in elementary school children in the city of Surakarta. This research uses a descriptive analysis research design. The population in the study were children aged 6-8 years in Danukusuman Surakarta totaling 100 respondents. Samples were taken using total sampling technique. The diagnosis of pediculosis capitis is made on the skin and hair area of the head and intensity helminth enforced use method Kato katz from fecal samples by calculating the number of worm parasite eggs per gram of feces (EPG). Based on research conducted on 100 respondents, the results showed that 29 (29%) respondents had pediculosis capitis and cases of helminthiasis showed that 2 respondents (2%) had Ascari  lumbricoides and Trichuris trichiura with a total of 24 epg of parasites each with a light infection intensity. From the results of this study, it was reported that the incidence of pediculosis capitis in children in Danukusuman was 29% and helminth infections were 2% of cases with a mild degree of infection.